Cochlear signal intensity changes in vestibular schwannoma: a balanced fast field-echo MRI study - Takeda, Hiroko; Fujita, Takeshi; Kanda, Tomonori; Uozumi, Yoichi; Uehara, Natsumi; Yokoi, Jun; Kakigi, Akinobu; Sasayama, Takashi; Nibu, Ken-ichi (Frontiers in Neurology, 2025)
IntroductionVestibular schwannoma (VS) is a benign tumor associated with cochlear degeneration and sensorineural hearing loss (SNHL). This study aimed to evaluate cochlear signal intensity in VS patients using balanced fast field-echo (bFFE) magnetic resonance imaging (MRI) and to explore its relationship with tumor size, hearing loss, and postoperative changes.MethodsA retrospective analysis was conducted on 165 VS patients and 30 SNHL control patients who underwent bFFE MRI at Kobe University Hospital from 2008 to 2019. Cochlear signal intensity was measured bilaterally using regions of interest (ROIs), and signal intensity ratios (affected/normal) were calculated. Statistical analyses included linear regression and ANOVA to evaluate correlations with hearing levels, tumor size, and postoperative changes.ResultsVS patients exhibited significantly lower cochlear signal intensity ratios on the affected side compared to controls (75.3% vs. 100%, p < 0.0001). Correlations between cochlear signal intensity ratios and hearing levels were significant in Koos grade I tumors but not in higher-grade tumors. Tumor size was negatively correlated with cochlear signal intensity ratios in Koos grade II–IV tumors. Postoperatively, signal intensity normalized within 1–2 years, irrespective of hearing preservation.DiscussionDecreased cochlear signal intensity in VS patients may indicate protein concentration changes due to tumor secretions. bFFE MRI effectively captures these changes, providing insights into cochlear physiology and tumor impact.ConclusionbFFE MRI is a reliable tool for assessing cochlear signal intensity in VS patients, offering potential for improved tumor evaluation, surgical planning, and postoperative monitoring.